Guinea-Bissau : Use of Fund Resources; Request for Third Purchase Under Emergency Post-Conflict Assistance; Staff Report; Staff Supplement; Press Release; and Statement by the Executive Director for Guinea-Bissau. (IMF Staff Country Reports; Country Report, 2009)
Global economic developments in Guinea-Bissau, especially lower export demand and prices, are expected to slow growth significantly and put pressure on the balance of payments. The 2009 fiscal framework aims to stabilize public finances and avoid new domestic arrears. The authorities are requesting a third Emergency Post-Conflict Assistance (EPCA) purchase of 12.5 percent of quota to support their 2009 economic framework. A third EPCA purchase would give them time to demonstrate a track record of policy performance that could pave the way for a new Poverty Reduction Growth Facility arrangement.